A review of hands-on based conservative treatments on pain in recreational and elite athletes - Fleckenstein, J.; Banzer, W. (Science & Sports, 2019)
Objectives: Acute pain in sports tells us what not to do. Persisting pain limits the athletes` activity and threatens his career. The reduction of pain is sought being highly beneficial for the sportsman, as it is shown that pain has only a weak connection to injury but a strong connection to the body image. Thus, pain therapy in sports medicine is a primary need of the athlete. Principle treatment goals are pain relief and return to play as quick as possible. Therapies in sports should primarily focus on conservative than on invasive approaches, with drugs being avoided as far as possible. There is a broad range of treatment approaches that could be applied in concert based on scientific and clinical decision making to reduce symptom severity, pain-associated dysfunction, and the risk of pain to be a tremendous cut in an elite athlete's career. Knowledge on this non-pharmacologic conservative pain medicine should not be restricted to health professionals, but the whole entourage of the athlete. This review highlights the current evidence with a focus on recreational and elite athletes. Based on their clinical evidence, it is hands-on techniques that can be recommended (Grade A: nerve blocks and injection techniques, ultrasound and laser therapy, manipulation mobilization, massage and traction; Grade B: acupuncture and dry needling). The occurrence of possible side-effects is, as far as reported, very unlikely. However, the methodological quality of the majority of retrieved studies limits the overall generalizability. Conclusion: Conservative non-pharmacologic therapies reflect an adequate strategy to relief pain in elite athletes. Chronic states of pain reflect more complex scenarios requiring further comprehensive techniques. Future research should thus also address multimodal approaches combining several of the mentioned therapies.